A bibliometric analysis and review of water resources carrying capacity using rené descartes’s discourse theory - Yang, Xiaojing; Sun, Boyang; Lei, Sheng; Li, Fapeng; Qu, Yanping (Frontiers in Earth Science, 2022)
Water Resources Carrying Capacity is an important indicator of water sustainable and economic development, yet few studies investigated a bibliometric analysis of Water Resources Carrying Capacity research. In this research, we proposed a four-staged bibliometric analysis method for Water Resources Carrying Capacity studies following the René Descartes’s Discourse on the Method guidelines which makes the bibliometric analysis process more systematic. Our four-staged bibliometric analysis method contains a refined screening process of the records, which can successfully delete poorly correlated data from tens of thousands of data within a short period of time and determined the subject-related data. The screening results shortlisted 271 records from an initial 16,769. We further conducted a complete bibliometric, statistical and meta-analysis of the 271 records. The results showed that China is the major country that conducts research on Water Resources Carrying Capacity. Modeling in various forms and system dynamics are the mainstream methods of Water Resources Carrying Capacity research. Water Resources Carrying Capacity is intrinsically linked to population carrying capacity, groundwater resources, urbanization and water shortage. Based on a comprehensive analysis of the research of Water Resources Carrying Capacity, we divided the research progress into five stages lastly. The method proposed in this research can provide reference for future bibliometric studies.